Enhancing Acne Care Through Design Thinking: UI/UX Blueprint for Dermist, a Teledermatology Application - Elsana Bekti Nugroho; Ellya Zulaikha (Dinasti Review, 2025)
Acne is one of the most common skin diseases worldwide. Most patients often resort to self-experimentation with skincare products. Accessibility to dermatological consultations is limited by the lack of on-demand, online services. In addition, treatments often do not address individual skin concerns. With the emergence of telemedicine in the digital era, this research aims to develop a platform tailored to acne concerns to improve acne care by providing accessible, convenient, and personalized dermatological consultations. The study employed a design thinking methodology. Preliminary data were collected to explore potential solutions for women with acne. In-depth interviews during the Empathize stage helped identify user needs and pain points. In the Define stage, insights were translated into problems and solutions using user persona and value proposition canvas. The platform's blueprint was developed with the use of affinity diagrams, information architecture, and user flow. After wireframing, user interface (UI) and user experience (UX) design, the prototype was tested through in-depth interviews and usability testing using Maze.co and system usability score (SUS). Key features included personalized skincare routines, photo scanning for skin analysis, interactive consultation booking, skincare purchasing, a daily check-in feature, and educational modules. Testing with Maze.co revealed a usability score of 94 with a misclick rate of less than 10% across all tasks. Additionally, the application achieved an SUS score of 83.75.